2021
DOI: 10.1093/biolre/ioab036
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin: a neuropeptide induced by hCG in the human and rat ovary during the periovulatory period

Abstract: Neurotensin (NTS) is a tridecapeptide that was first characterized as a neurotransmitter in neuronal cells. The present study examined ovarian NTS expression across the periovulatory period in the human and the rat. Women were recruited into this study and monitored by transvaginal ultrasound. The dominant follicle was surgically excised prior to the LH surge (preovulatory phase) or women were given 250 μg hCG and dominant follicles collected 12-18 h after hCG (early ovulatory), 18-34 h (late ovulatory) and 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The presence of receptors within the oocyte suggests a paracrine role for estrogens in its maturation process or an inducing role for other directly involved factors, such as neurotensin. Documentation on the role of this peptide in the ovary is very scarce, and only recently has its expression during the periovulatory period been described in human and rat ovaries with hCG hormone-induced expression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of receptors within the oocyte suggests a paracrine role for estrogens in its maturation process or an inducing role for other directly involved factors, such as neurotensin. Documentation on the role of this peptide in the ovary is very scarce, and only recently has its expression during the periovulatory period been described in human and rat ovaries with hCG hormone-induced expression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that these NTS-ir pituitary cells are also ERα-ir and that the distribution pattern of NTS-ir cells in the pituitary gland partially depends on gonadal function [ 6 , 20 , 21 , 22 , 23 ]. Recent studies using experimental models have confirmed NTS expression in gonads [ 24 , 25 ]. These authors show that granulosa cells are likely the primary or only source of NTS in the ovulatory follicle, although it has also been put forward as a paracrine mediator of ovulation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies elaborated on the role of neurotransmitters and neuropeptides during ovulation. The neuropeptide neurotensin (NT) was first identified in bovine hypothalamus (Carraway & Leeman, 1973) and was reported to be expressed in other species and tissues, including humans and rat ovaries during the periovulatory period (Al-Alem et al, 2021). Soon several reports demonstrated role for NT in multiple aspects of ovarian function and sperm capacitation (Reinecke, 1987;Dissen et al, 1996;Hiradate et al, 2014;Cerny et al, 2015;Sakumoto et al, 2015;Umezu et al, 2016).…”
Section: Neuronal Signaling In Oocyte Maturationmentioning
confidence: 99%
“…1 Recent studies have identified neurotensin (NTS) as a paracrine mediator of ovulation. [3][4][5] This 13-amino acid peptide is produced primarily by the granulosa cells in response to the LH surge and is transiently but highly upregulated around the time of ovulation in the human, monkey, rat, and mouse ovary. [3][4][5] NTS exerts its effect directly on ovarian endothelial cells.…”
Section: Introductionmentioning
confidence: 99%